Analysis of the ferrous benzoic methylthymol-blue gel dosimeter in low-dose-level measurements. (August 2020) - Parwaie, Wrya; Geraily, Ghazale; Shirazi, Alireza; Shakeri, Ahmad; Massumi, Hassan; Farzin, Mostafa
Abstract: Despite the advantages of the Fricke gel dosimeter, the use of this tool is associated with limitations in the patient-specific quality assurance due to high uncertainty in the measurement of low dose levels. The present study aimed to develop a Fricke-based gel dosimeter that is sensitive to low dose levels. For this purpose, benzoic acid was added to the ferrous methylthymol-blue gel dosimeter, and the concentration of components was changed. The irradiation of samples was performed using the linear accelerator machine. The ultraviolet–visible spectrophotometer was employed to quantify the dose-responses, auto-oxidation rate, and energy and dose rate dependency. The diffusion rate was measured with magnetic resonance imaging. The maximum difference in absorbance occurred at 439 and 619 nm between un-irradiated and irradiated samples. The sensitivity of the gel dosimeter decreased with an increase in the concentration of methylthymol-blue. The dose-response curve of the gel dosimeter at 439 nm demonstrated high sensitivity in the dose range 0–200 cGy. The auto-oxidation and diffusion rates of the gel dosimeter equaled 0.00106 ± 0.00006 h −1 and 0.845 ± 0.013 mm 2  h -1, respectively. The optimized formulation was capable to measure the low dose levels with sufficient confidence. Future studies are needed to evaluate the performance of the optimized formulation in clinical situations. Highlights: A high sensitivity formulation of Fricke gel is introduced to low doses. There is an excellent dose response at 439 nm in the dose range 0–200 cGy. The gel sensitivity decreased with an increase in the MTB concentration.